Navigating the Jakarta Islamic Index During the Pandemic: An Analysis of Abnormal Returns and Trading Volume Dynamics - Indah Amalia Putri; Ferry Khusnul Mubarok (Green Economics Review, 2024)
This study aims to analyze the differences in abnormal returns and trading volume activity before and during the COVID-19 pandemic in companies listed on the Jakarta Islamic Index (JII). The COVID-19 pandemic has significantly impacted the global and national economy, including Indonesia's Islamic finance sector. This study presents a novel contribution by examining the effects of COVID-19 on Indonesia’s Sharia-based stock market, a relatively underexplored area in Islamic finance literature. The research method used is an event study, utilizing secondary data of daily stock prices and trading volume activity for 21 days before and 21 days after the first COVID-19 case announcement on March 2, 2020. The sample comprises 30 stocks listed on the JII index. The analysis reveals significant differences in abnormal returns and trading volumes before and after the COVID-19 announcement, reflecting shifts in market responses to the global health crisis. The implications of this study provide valuable insights for investors, policymakers, and Sharia-compliant companies on the sensitivity of Islamic markets to major events like pandemics. Additionally, these findings are expected to aid in developing risk mitigation strategies for the Islamic stock market to address future global uncertainties.